Glossary of Geotechnics - Swedish Centre for Terminology (Institute for Language and Folklore, 2023)
Multilingual terminology glossary containing terms from the geotechnical field. The glossary has been created by the Swedish Centre for Terminology (TNC) in close cooperation with the Swedish Geotechnical Society. The glossary contains 458 in Swedish, in addition some terms have been translated to Russian, Finnish, German, French and English.

Flerspråkig terminologisamling som rör geotekniska termer. Ordlistan har utarbetats av Tekniska nomenklaturcentralen i nära samarbete med Svenska Geotekniska föreningen. Samlingen innehåller 458 termer på svenska. Somliga termer är översatta till ryska, finska, tyska, franska och engelska.
Geoteknisk ordlista
Keywords: multilingualism; flerspråkighet; terminology; terminologi; Term glossary; Termlista; Geotechnics; Geoteknik; Languages and Literature; Språk och litteratur